2020
DOI: 10.1026/1616-3443/a000592
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Psychologische Folgen für Familie, Kinder und Partnerschaft

Abstract: Zusammenfassung. Dieser Beitrag soll die spezifischen Auswirkungen auf Familien, Kinder und Partnerschaften diskutieren, die sich durch die Covid-19-Pandemie einstellen könnten. Er ist primär gedacht für alle professionellen Helfer, die in Kontakt mit betroffenen Familien stehen. Die COVID-19-Pandemie stellt eine akute Bedrohung für das familiäre Wohlergehen dar, da sie mit psychologischen Reaktionen (z. B. Angst, Depression, Wut) der Familienangehörigen sowie sozialen Belastungen, die durch finanzielle Unsich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…While many studies have already shown that regulatory measures to contain the pandemic such as contact restrictions, short-time work, school closures etc. have a negative impact (35,36), we were able to show for the first time in our study that maternal attachment representation and the associated coping skills and corresponding parental behavior also significantly influence children's mental health during the pandemic.…”
Section: Discussionsupporting
confidence: 50%
“…While many studies have already shown that regulatory measures to contain the pandemic such as contact restrictions, short-time work, school closures etc. have a negative impact (35,36), we were able to show for the first time in our study that maternal attachment representation and the associated coping skills and corresponding parental behavior also significantly influence children's mental health during the pandemic.…”
Section: Discussionsupporting
confidence: 50%
“…Applying the stress transactional model [STM; 2,4], stress from outside the partnership, i.e., extradyadic stress, can increase intradyadic stress and impair mental well-being and relationship satisfaction [5,6]. In the context of the COVID-19 pandemic in particular, both extradyadic stress (e.g., related to pandemic-related restrictions or increase in anxiety and worry) [7][8][9] and intradyadic stress (e.g., more conflicts and dysfunctional dyadic processes) [1,10] were prone to negatively affect relationship satisfaction.…”
Section: Being a Couple Throughout A Worldwide Pandemicmentioning
confidence: 99%